The world Jesus knew : a curious kid's guide to life in the first century - Olson, Marc, 1971-; Maybank, Jemima (Minneapolis, MN : Sparkhouse Family, 2017)
Jesus often told stories using everyday objects to help his listeners understand life with God. But for most of us, the deep imagery and meaning behind those objects has been lost to history. This book helps kids discover the world Jesus lived in through maps, charts, graphs, and other infographic elements. They'll learn about the culture Jesus lived in--:his Jewish religion, the power of the ruling Roman Empire, the role of fishermen and carpenters and shepherds.
Keywords: Geography; Manners and customs; Travel; Manners and customs; Geography; Travel; JUVENILE NONFICTION / Architecture; JUVENILE NONFICTION / History / Ancient; JUVENILE NONFICTION / History / Middle East; JUVENILE NONFICTION / People & Places / Middle East; JUVENILE NONFICTION / Religion / Bible Stories / General